Development of Coastal Ecotourism MSMEs through Puger Beach Destination Management Training - Totok Hendarto; Yogantara Setya Dharmawan (Unram Journal of Community Service, 2025)
This community service program aims to strengthen coastal micro, small, and medium enterprises (MSMEs) and ecotourism development at Puger Beach, Jember Regency, Indonesia. Puger is a traditional fishing hub with growing ecotourism potential, yet it faces constraints in destination management, product innovation, digital marketing, and stakeholder coordination. Using a participatory approach, the program involved 40 purposively selected MSMEs (fish cuisine, tourist boats, beach stalls, and handicrafts) through stages of needs assessment, training, mentoring, and evaluation. Training modules covered coastal destination management, service quality, branding, and digital promotion, followed by intensive on-site mentoring and collaborative development of promotional media. Pre- and post-intervention data were collected using questionnaires, observation, and interviews. The results show improved MSME capacities in arranging business spaces, applying basic hospitality standards, and utilising social media for promotion. Tourism boat providers and food vendors reported higher visitor numbers and short-term income growth, while handicraft producers began to reposition their products for tourism markets. The program also stimulated cleaner environmental practices and stronger collaboration between MSMEs, local leaders, and village government. These findings indicate that community-based destination management training can be an effective strategy for enhancing local economic resilience while supporting sustainable coastal ecotourism.